Risk of congenital cytomegalovirus infection among HIV‐exposed uninfected infants is not decreased by maternal nelfinavir use during pregnancy. Issue 6 (18th November 2015) - Gantt, Soren; Leister, Erin; Jacobsen, Denise L.; Boucoiran, Isabelle; Huang, Meei‐Li; Jerome, Keith R.; Jourdain, Gonzague; Ngo‐Giang‐Huong, Nicole; Burchett, Sandra; Frenkel, Lisa
Abstract : Background: Congenital cytomegalovirus (cCMV) infection is common among infants born to HIV‐infected women. Nelfinavir (NFV), an antiretroviral drug that is safe during pregnancy, inhibits CMV replication in vitro at concentrations that standard doses achieve in plasma. We hypothesized that infants born to women receiving NFV for prevention of mother‐to‐child transmission of HIV (PMTCT) would have a reduced prevalence of cCMV infection. Methods: The prevalence of cCMV infection was compared among HIV‐uninfected infants whose HIV‐infected mothers either received NFV for> 4 weeks during pregnancy (NFV‐exposed) or did not receive any NFV in pregnancy (NFV‐unexposed). CMV PCR was performed on infant blood samples collected at <3 weeks from birth. Results: Of the 1, 255 women included, 314 received NFV for> 4 weeks during pregnancy and 941 did not receive any NFV during pregnancy. The overall prevalence of cCMV infection in the infants was 2.2%, which did not differ by maternal NFV use. Maternal CD4 T cell counts were inversely correlated with risk of cCMV infection, independent of the time NFV was initiated during gestation. Infants with cCMV infection were born 0.7 weeks earlier ( P = 0.010) and weighed 170 g less ( P = 0.009) than uninfected infants. Conclusion: Among HIV‐exposed uninfected infants, cCMV infection was associated with adverse perinatal outcomes. NFV use in pregnancy was not associated with protection against cCMV. Safe and effective strategies to prevent cCMV infection are needed. J. Med. Virol. 88:1051–1058, 2016 . © 2015 Wiley Periodicals, Inc.